Corrosion inhibition of mild steel in acidic medium by poly (aniline-co-o-toluidine) doped with p-toluene sulphonic acid - Srivastava V.; Singh M.M. (My University, 2025)
The corrosion behaviour of mild steel in 0.5 M H2SO4 solution containing various concentrations of a p-toluene sulphonic acid doped copolymer formed between aniline and o-toluidine was investigated using weight loss, polarization and electrochemical impedance techniques. The copolymer acted as an effective corrosion inhibitor for mild steel in sulphuric acid medium. The inhibition efficiency has been found to increase with increase in inhibitor concentration, solution temperature and immersion time. Various parameters like E a for corrosion of mild steel in presence of different concentrations of inhibitor and ΔG ads, ΔH 0, ΔS 0 for adsorption of the inhibitor, revealed a strong interaction between inhibitor and mild steel surface. The adsorption of this inhibitor on the mild steel surface obeyed the Langmuir adsorption equation. © 2010 Springer Science+Business Media B.V.